Lactobacillus plantarum IS-20506 Probiotic Restores Galectin-4 and Myosin-1a Expressions in Duodenum, Jejunum and Ileum of Lipopolysaccharide-induced Rats - Reza Gunadi Ranuh; Alpha Fardah Athiyyah; Andy Darma; Wibi Riawan; Ingrid Suryanti Surono; Ferry Sandra; Subijanto Marto Sudarmo (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Galectin-4 and Myosin-1a are important proteins for normal intestinal brush border structure and composition. Damage of these proteins by inflammation may alter digestion, absorption and barrier function. Probiotic has been widely known in maintaining gut health. However, the molecular mechanism of Lactobacillus plantarum IS-2056 probiotic in repairing intestinal brush border is not well defined. Therefore, current study was conducted by investigating the Galectin-4 and Myosin-1a expressions in a rodent model.METHODS: Male Wistar rats were induced with/without lipopolysaccharide (LPS) and treated with/without L. plantarum IS-2056 probiotic. On the seventh day, duodenum, jejunum, and ileum were collected and analyzed with western blot and immunohistochemistry for Galectin-4 and Myosin-1a expressions.RESULTS: Rats administrated with L. plantarum IS-2056 probiotic showed significant increase of Galectin-4 and Myosin-1a expressions in duodenum, jejunum, and ileum compared to the control group (p<0.05). While in control group, Galectin-4 level tended to increase in more distal of intestinal segment and Myosin-1a level tended to decrease in more distal intestinal segment.CONCLUSION: L. plantarum IS-20506 probiotic may facilitate the repairment of damaged intestinal brush border as demonstrated by significant restoration of Galectin-4 and Myosin-1a expressions in duodenum, jejunum, and ileum of LPS-induced rats.KEYWORDS: Lactobacillus plantarum, IS-20506, probiotic, galectin-4, myosin-1a, duodenum, jejunum, ileum